2017
DOI: 10.1002/gj.3041
|View full text |Cite
|
Sign up to set email alerts
|

Early Paleozoic arc magmatism and metamorphism in the northern Qilian Block, western China: Petrological and geochronological constraints

Abstract: The Datong–Menyuan Complex, located in the northern margin of the Qilian Block, is composed dominantly of high‐grade metamorphic rocks covered by a Paleozoic–Mesozoic sedimentary sequence. In this study, we present petrographic observation, conventional thermobarometry and P–T pseudosection modelling, whole‐rock major and trace geochemistry, zircons U–Pb dating and Hf isotopic data together, to reveal the relationship between the magmatism and metamorphism along the northern margin of the Qilian Block. The ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 137 publications
(257 reference statements)
1
34
0
Order By: Relevance
“…Sr-Nd-Pb isotopes and trace elemental geochemistry of the basaltic rocks from the Yushigou and Dongcaohe ophiolites suggested that the North Qilian Ocean has a tectonic affinity with the Proto-Tethyan Ocean (Hou et al, 2006;Tseng et al, 2007). Studies on Early Cambrian volcanic-intrusive rocks show that northward subduction of the North Qilian oceanic slab initiated at ~520 Ma (Xia et al, 2012;Chen et al, 2014), although some researchers also inferred a southward subduction for the North Qilian Ocean (Peng et al, 2017a(Peng et al, , 2017b. Geochronological and geochemical data of the Jiugequan ophiolite imply that the extension of the back-arc basin in the North Qilian initially occurred at ~490 Ma (Xia and Song, 2010).…”
Section: Geological Backgroundmentioning
confidence: 99%
“…Sr-Nd-Pb isotopes and trace elemental geochemistry of the basaltic rocks from the Yushigou and Dongcaohe ophiolites suggested that the North Qilian Ocean has a tectonic affinity with the Proto-Tethyan Ocean (Hou et al, 2006;Tseng et al, 2007). Studies on Early Cambrian volcanic-intrusive rocks show that northward subduction of the North Qilian oceanic slab initiated at ~520 Ma (Xia et al, 2012;Chen et al, 2014), although some researchers also inferred a southward subduction for the North Qilian Ocean (Peng et al, 2017a(Peng et al, , 2017b. Geochronological and geochemical data of the Jiugequan ophiolite imply that the extension of the back-arc basin in the North Qilian initially occurred at ~490 Ma (Xia and Song, 2010).…”
Section: Geological Backgroundmentioning
confidence: 99%
“…Zircon U–Pb geochronology revealed that these magmatic arc rocks intruded between c . 510 and 460 Ma (Huang et al., ; Peng et al., ). Its Neoproterozoic magmatic–tectonometamorphic history is similar to that of the South China Block, which suggests a close affinity between them (e.g.…”
Section: Geological Backgroundmentioning
confidence: 99%
“…It was extensively intruded by early Palaeozoic mafic and granitic magmatism with arc-related geochemical features (e.g. Huang et al, 2015;Peng et al, 2017;Yan et al, 2015). Zircon U-Pb geochronology revealed that these magmatic arc rocks intruded between c. 510 and 460 Ma (Huang et al, 2015;Peng et al, 2017).…”
Section: Regional Geologymentioning
confidence: 99%
“…A much wider theme is addressed in the paper by Wu et al () who examine the sedimentary sequences in cratonic basins, especially Yangtze Craton, during the break‐up of Rodinia. In the paper by Peng et al (), the focus of the study was on Early Paleozoic arc magmatism and metamorphism in the northern Qilian Block. The final three papers in this region by H. Feng et al (); Shu et al (); and Z. Tang et al () all concentrate on aspects of Jurassic basin sedimentation characteristics, and provenance in the northern Qaidam Block.…”
Section: Volume 1 Structure and Main Themesmentioning
confidence: 99%